Bladder Draining Methods - D. D. Lukashev; T. G. Mikhailikov; P. A. Yartsev (Неотложная медицинская помощь)
ABSTRACT The article provides a historical review of the literature describing the evolution of bladder drainage and the types of urinary catheters currently in use. Complications of various drainage methods are classified and described, and measures for their prevention are proposed.AIM OF STUDY To study bladder draining methods, their advantages and disadvantages, possible complications of each method.OBJECTIVES To assess the indications for use of each drainage method, to focus the attention of health workers on the possibility of choosing the optimal method for bladder draining, depending on the clinical situation.